PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI POLITEKNIK LP3I JAKARTA - Agung Edi Rustanto (POLITEKNIK LP3I JAKARTA, 2018)
Abstract Changes in employee performance can always change and fluctuate, but the fundamental changes are changes caused by culture in an organization. Performance that has been affected by organizational culture will be more firmly embedded in employees. Basically there are several things that can influence fundamentally on employee performance but organizational culture factors can be called very interesting factors to be discussed in more depth. This study aims to analyze the influence of organizational culture on employee performance at the Polytechnic LP3I Jakarta. Through the results of this study it can be seen that how much organizational culture influences employee performance, as well as the influence of other factors outside the organizational culture. The results of this study can show how important organizational culture is in its role in employee performance. The method used in this research is descriptive quantitative method. Data analysis was carried out through simple linear regression. The research instrument used was a questionnaire. The result of this study is that organizational culture has a significant effect on employee performance at the Polytechnic LP3I Jakarta. Organizational culture has an effect of 0.5% on employee performance at the Polytechnic LP3I Jakarta.Keywords: organizational culture, performance, employee.